2002
DOI: 10.3327/taesj2002.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Human Error for a Seismic PSA

Abstract: This paper describes a model for human error probability (HEP) for seismic probabilistic safety assessments (PSAs) of nuclear power plants and its application. Considering the factors unique to seismic events such as level of seismic motion and stress to the operators, the authors adopted a model called a limited ramp model (LRM), where HEP is assumed to be the same as that for internal event PSAs for zero level of seismic motion, and then increases linearly with seismic level to a constant at a certain seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For example, Yokobayashi et al (2002) suggested that the HEP of a certain HFE to be accomplished within a short time period after the occurrence of an earthquake (i.e., a short-term HEP) is defined by 15 times of its HEP quantified without considering a seismic effect. In addition, they offered a hypothetical ramp model for a long-term HFE, which expresses the effect of a seismic intensity on the increase of an HEP (refer to Fig.…”
Section: Human Reliability Analysis Under a Seismic Eventmentioning
confidence: 99%
“…For example, Yokobayashi et al (2002) suggested that the HEP of a certain HFE to be accomplished within a short time period after the occurrence of an earthquake (i.e., a short-term HEP) is defined by 15 times of its HEP quantified without considering a seismic effect. In addition, they offered a hypothetical ramp model for a long-term HFE, which expresses the effect of a seismic intensity on the increase of an HEP (refer to Fig.…”
Section: Human Reliability Analysis Under a Seismic Eventmentioning
confidence: 99%
“…When major earthquakes occur, nuclear reactors generally shut down automatically. However, operators must possess steady judgment to handle the malfunctions and defects resulting from earthquakes and to safely bring the reactor to cold shutdown (Shibata and Takada 1995;Yokobayashi et al 2002). To prevent erroneous judgments that aggravate disaster situations, as happened previously at Three Mile Island (Jang et al 2016) and Chernobyl (Salge and Milling 2006), operators regularly train using training simulators to respond steadily and appropriately during major earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the impact of earthquakes on operator performance by setting up a simple simulated operation panel on a shaking table (Shibata 1987; Kitada et al 1994;Park et al 2018; Kim et al 2019;Yokobayashi et al 2002). Shibata (1987) set up a cathode ray tube (CRT) and keyboard on a shaking table and conducted an experiment in which subjects typed in the letters appearing on the CRT during vibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ramp model presented by Yokobayashi et al (1998), the operator performance is modeled by a linear relationship between the seismic-induced HEP and the PGA until a maximum ground acceleration level L is reached.…”
Section: Operator Actionsmentioning
confidence: 99%